Pluralism in the Fiqh Sosial’s Perspective - Tutik Nurul Janah; Umdah el Baroroh (Santri: Journal of Pesantren and Fiqh Sosial, 2021)
Methodologically, Fiqh Sosial encourages the resolution of people's problems by using the qauli and manhaji schools of thought. The qauli school of choice takes precedence. If the qauli school is unable to provide a solution to the problems at hand, then the manhaji school of thought is used. Basically, the qauli school of thought is sufficient if it is used in solving basic pluralism problems. However, if the issue of pluralism has entered a more complicated domain, and the qauli school of thought is no longer sufficient, then the manhaji school of thought can be used. The implementation of the methodology of Fiqh Sosial in the issue of pluralism can be seen from the consistency of Kiai Sahal in harmonizing his thoughts and his daily life. Kiai Sahal shows an open mind in building relationships and collaborating with many people from various ethnic, religious and professional backgrounds. This paper is the result of research on pluralism in the perspective of Fiqh Sosial. This study aims to determine the concept of Fiqh Sosial regarding pluralism and the application of Fiqh Sosial methodology in responding to pluralism issues. This research is a qualitative research. This research is a literature study using descriptive methods.